2010
DOI: 10.4052/tigg.22.141
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Endogenous Ligands by C-Type Lectins:Interaction of Serum Mannan-binding Protein with Tumor-associated Oligosaccharide Epitopes

Abstract: Animal lectins have contributed greatly to understanding of the physiological significance of glycans in man and animals. Mannan-binding protein (MBP) binds to mannose, N-acetylglucosamine and L-fucose via the carbohydrate binding sites in its carbohydrate recognition domain (CRD). In pathogenic microorganisms, manno-oligosaccharides on the cell surface appear to be the major glycans involved in the interaction with MBP, whereas in human colorectal carcinoma SW1116 cells, which are endogenous target cells of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…MALDI mass spectrometry of the N-glycans released from CD26 by PNGase F suggested that complex-type N-glycans carrying a minimum of four Le a /Le b epitopes, arranged either as multimeric tandem repeats or terminal epitopes on multiantennary structures, are critically important for the high-affinity binding to MBP. On the basis of these observations, a hypothetical threedimensional model of the MBP-Le oligosaccharide complex was presented (26,27). In this study, we demonstrated that MBP recognizes human primary and metastatic colorectal carcinoma (Table II), and anti-CD3 staining (p = 0.0719) ( Table III), indicating that MBP stains colorectal carcinoma tissues, regardless of those factors.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…MALDI mass spectrometry of the N-glycans released from CD26 by PNGase F suggested that complex-type N-glycans carrying a minimum of four Le a /Le b epitopes, arranged either as multimeric tandem repeats or terminal epitopes on multiantennary structures, are critically important for the high-affinity binding to MBP. On the basis of these observations, a hypothetical threedimensional model of the MBP-Le oligosaccharide complex was presented (26,27). In this study, we demonstrated that MBP recognizes human primary and metastatic colorectal carcinoma (Table II), and anti-CD3 staining (p = 0.0719) ( Table III), indicating that MBP stains colorectal carcinoma tissues, regardless of those factors.…”
Section: Discussionmentioning
confidence: 80%
“…TO-PRO3 (blue, pseudo-color) was used for counter-staining. proposed structure of the MBP ligands isolated from SW1116 cells) (15,26,27).…”
Section: Mbp Recognizes Colorectal Tumor-derived Le B+ Glycansmentioning
confidence: 99%
“…These glycans are involved in many biological processes including tumor metastasis ( 47 ). Recent studies indicated that Type-I LacNAc-tandem repeats were isolated from SW1116 human colorectal carcinoma cell line ( 28 , 48 , 49 ) and shown as the specific ligands of the tumor-associated human galectin 3 ( 22 , 50 ). Type-I LacNAc-containing glycans can be utilized to gain novel insights about their functional roles, such as interactions with carbohydrate-binding proteins (e.g., galectin 3), fertilization, pathogen adhesion, and inhibitory activity against tumor cells.…”
Section: Synthesis Of Type-i Lacnac Repeating Oligosaccharidesmentioning
confidence: 99%
“…TACA-based antitumor vaccines have shown great potential and high specificity in cancer immunotherapy. Initially, these carbohydrate antigens were isolated from tumor cells only, instead of normal cells ( 23 , 27 , 28 ). To explore the biological significance of tumor-associated antigens or any endogenous glycans, acquiring a sufficient quantity of desirable carbohydrates represents an important task.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, such characteristic clusters can also signal an aberration tied to malignancy to the innate host-defence system, a surveillance mechanism described in Table 4. In fact, the correspondingly glycosylated glycoproteins CD26/CD98hc are reactive with the collectin mannan-binding lectin, an activator of the complement cascade [41].…”
Section: Activitymentioning
confidence: 99%